Microdissection and Chromosome Painting - Vicari, M. R. (2015)
The principle of chromosome microdissection technique is based on the identification of either a chromosome, chromosome arm or chromosome band for the subsequent removal of such target with the aid of a micromanipulator attached to an inverted microscope. Once the target is defined, whole chromosomes, or chromosomal regions, are directly isolated under an inverted microscope linked to a micromanipulator. Following dissection, chromosomal fragments pass through a step of amplification, using adapted methods of whole genome amplification (WGA) in order to increase the limited amount of DNA (Telenius et al. 1992; Zhang et al. 1992) and reduce the starting copies material (Fig. 1).